Multimodal Strategies for the Diagnosis and Management of Refractory Congestion. An Integrated Cardiorenal Approach - Rodríguez-Espinosa, Diana; Guzman-Bofarull, Joan; De La Fuente-Mancera, Juan Carlos; Maduell, Francisco; Broseta, José Jesús; Farrero, Marta (Frontiers in Physiology, 2022)
Refractory congestion is common in acute and chronic heart failure, and it significantly impacts functional class, renal function, hospital admissions, and survival. In this paper, the pathophysiological mechanisms involved in cardiorenal syndrome and the interplay between heart failure and chronic kidney disease are reviewed. Although the physical exam remains key in identifying congestion, new tools such as biomarkers or lung, vascular, and renal ultrasound are currently being used to detect subclinical forms and can potentially impact its management. Thus, an integrated multimodal diagnostic algorithm is proposed. There are several strategies for treating congestion, although data on their efficacy are scarce and have not been validated. Herein, we review the optimal use and monitorization of different diuretic types, administration route, dose titration using urinary volume and natriuresis, and a sequential diuretic scheme to achieve a multitargeted nephron blockade, common adverse events, and how to manage them. In addition, we discuss alternative strategies such as subcutaneous furosemide, hypertonic saline, and albumin infusions and the available evidence of their role in congestion management. We also discuss the use of extracorporeal therapies, such as ultrafiltration, peritoneal dialysis, or conventional hemodialysis, in patients with normal or impaired renal function. This review results from a multidisciplinary view involving both nephrologists and cardiologists.